Transform Your Heart Failure Treatment Approach: Conquering Svt and Pneumonia Challenges - Utami, Nabilah Puspa; Nugraha, Adriyawan Widya (Jurnal Komplikasi Anestesi, 2025)
In this complex case, an 81-year-old female presented with acute decompensated heart failure (ADHF), pneumonia, and SVT-induced tachyarrhythmia. Upon admission, she received meticulous therapy in the intensive care unit (ICU). The treatment regimen was multifaceted, aiming to address each condition effectively. Fluid balance was closely monitored and maintained. Pharmacological interventions played a crucial role, with digoxin administered initially to manage SVT, alongside medications targeting heart failure including clopidogrel, atorvastatin, spironolactone, candesartan, and furosemide. Antibiotic therapy was initiated promptly following consultation with a pulmonologist, comprising ceftriaxone, levofloxacin, and methylprednisolone for pneumonia management. Additionally, regular nebulizations with salbutamol-ipratropium were administered. By the third day of hospitalization, significant improvement was observed, allowing for the patient's transfer to a general medical ward. This case underscores the importance of a comprehensive therapeutic approach in managing complex medical conditions, such as ADHF exacerbated by SVT and pneumonia, to achieve optimal patient outcomes.